Strikelron OnDemand Web Services for Microsoft Excel Web Services for the masses. - Frohnhoefer, Keith
There was a time when the term "spreadsheet" simply meant columns of data that were summed up. Although this is all the functionality some people require, Excel has evolved into a much more powerful tool. Users now have the ability to create complex formulas with built-in functions such as MAX, SIN and SUMIF. They can link workbooks together and not only import data directly from a database, but mirror many database capabilities using VLOOKUP and Pivot Tables. Business administrators can use Excel to automata many of their daily tasks, where they used to require the IT department to develop a database and application. With this traditional power, concepts such as primary and foreign keys are no longer foreign to the common workers.